Parental‐couple separation during the transition to parenthood. Issue 5 (26th February 2021) - Gamgam Leanderz, Åsa; Hallgren, Jenny; Henricson, Maria; Larsson, Margaretha; Bäckström, Caroline
Abstract: Aim: To evaluate factors associated with parental separation during the parenthood transition. Design: Prospective, longitudinal and explorative. Methods: This is a quantitative longitudinal study of N784 subjects throughout the pregnancy journey with multivariate regression analysis of survey data derived from three validated measurement scales; the Sense of Coherence scale, the Multidimensional Scale of Perceived Social Support and the Perceived Quality of the Dyadic Relationship scale conducted 2014–2016. Results: N17 participants separated at 2 years. Parental separation was significantly greater for those women and partners with low or changing sense of coherence, perceived social support and perceived quality of the parental‐couple relationship indexes. Partners with a change in sense of coherence ( p : .003) and perceived quality of the parental‐couple relationship ( p : .020) between 1 week and 2 years were at greater risk for separation. Attending professional preparatory support with a partner for women ( p : .013) and attending the "Inspirational Lecture" for partners ( p : .046) were, to a lesser extent, associated with a risk of parental separation.